2016
DOI: 10.1177/0021998316682603
|View full text |Cite
|
Sign up to set email alerts
|

Glass/epoxy structural composites with interleaved nylon 6/6 nanofibers

Abstract: Nylon 6/6 nanofibers of diameter 80–100 nm were electrospun on bidirectional E-glass fabric. The fabric with nanofibers on one surface was used to fabricate glass/epoxy structural composites, through resin film infusion. Mechanical properties of composites with interleaved nylon 6/6 nanofibers were found to be substantially improved from that of the control specimens fabricated under identical conditions, but without nanofibers. Compressive strength of composites showed over 30% increase, while interlaminar sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…For glass and carbon fiber‐reinforced polymer composites, it is significant to infuse polymer into each and every fiber tow. If polymer is not able to infuse well, voids could be introduced, resulting in a degradation of the mechanical properties 17,28,30 . A series of experiments were conducted to increase the wettability of nanofibers and bubble‐free nanocomposite films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For glass and carbon fiber‐reinforced polymer composites, it is significant to infuse polymer into each and every fiber tow. If polymer is not able to infuse well, voids could be introduced, resulting in a degradation of the mechanical properties 17,28,30 . A series of experiments were conducted to increase the wettability of nanofibers and bubble‐free nanocomposite films.…”
Section: Resultsmentioning
confidence: 99%
“…Anand et al . investigated the influence of interleaved nylon 6 nanofibers on a glass/epoxy structural composite 17 . They reported improvement in the compression, interlaminar shear strength and low‐velocity impact properties of the glass/epoxy composite with interleaved nylon 6 nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that nanofibers could increase the adhesion strength between AL and laminate, which led to a decrease of the damaged area between 42% and 62% depending on the impact energy level ( Figure 5). Anand et al [30] used a new method for producing nanomodified laminates. In this method, the nanofibers were firstly electrospun on dry glass fibers, then cast resin film was transferred to them.…”
Section: Composite Laminates Toughened By Polymeric Nanofibersmentioning
confidence: 99%
“…High performance thermoplastics with high modulus and high glass transition temperatures have been reported to be efficient in improving the fracture toughness of laminated composites [27][28][29][30][31][32][33][34]; they can be cured and implemented during the manufacturing process of the laminated composites [35]. One of the constraints of these interleave materials is the requirement of a good chemical and physical compatibility between the interleaving thermoplastic and the bulk thermoset resin.…”
Section: Introductionmentioning
confidence: 99%